Acute Care General Surgery : Workup and Management - Dangleben, Dale A.; Madbak, Firas G. (Springer International Publishing : Imprint: Springer, 2017)
Acute Care General Surgery provides a succinct focused overview of a myriad of general surgical emergencies. Each chapter has a concise, practical framework on the workup and management of a specific topic. The book covers a wide array of pathology from the more common appendicitis, diverticulitis and cholecystitis to those less frequently encountered such as toxic megacolon, Fournier's gangrene and volvulus. Learning objectives for each chapter are clearly defined. In addition to differential diagnosis, the work up and management is comprehensively discussed. In addition, a pithy clinical pearl is included to serve as a memory aid for each diagnosis. Upon reviewing this volume, clinicians who encounter the acute care surgical patient in their practices will be better equipped to rapidly assess, evaluate, diagnose and managing their complex and often challenging problems.